Distinguished VT and SVT with aberrations in Young Aged Patient : A Case Report - Wirawan, Pradnya (Universitas Airlangga, 2025)
Background: Arrhythmia with tachycardia is one of the emergencies that is often found in the ER. However, very often VT and SVT with aberrant especially in young aged patients make general practitioners confused about taking further action. Case Summary: A 19 year old male patient came to the ER with complaints of palpitations since 30 minutes. From the physical examination, the BP was 102/60, the pulse was 160x/minute. The ECG showed signs of arrhythmia with tachycardia. Conclusion: Treatment for SVT is clearly very different from VT, but sometimes making a diagnosis in the ER is still a challenge. It is necessary to looking at the history and the ECG so that the therapy given is appropiate. – Highlight: 1. This case underscores the diagnostic challenge of distinguishing VT from SVT with aberrancy in young patients presenting with tachycardia. In this 19-year-old male with stable vitals and a wide-complex tachycardia, careful ECG interpretation and clinical history were essential to guide appropriate therapy and avoid mismanagement.